Analysis of pre-service teachers’ argumentation-based academic writing process - Direkci, Bekir; Akbulut, Serdar; Şimşek, Bilal; Gülmez, Mevlüt; Nalçacıgil Çopur, Emel (Frontiers in Psychology, 2022)
The purpose of this research is to examine the participating students’ argumentation-based academic writing processes and the contributions of these processes to the students' academic writing skills. The participants of the study, which was conducted through mixed method research design, were a group of 53 pre-service Turkish Teachers who are in their first year of Turkish education programme at a state university in Turkey during the 2020-2021 academic year. In this research, the data were obtained through student products, rubrics, reflective participant diaries and a semi-structured interview form. SPSS 23 was used in the analysis of the quantitative data, and NVivo 12 programs were used in the analysis of qualitative data. When the results of the analyses are considered in general, it can be deduced that academic writing practices based on argumentation contributed to the development of students in the dimensions of "subject and content", "organization", "language use", "citation" and "writing process". In the data obtained from the reflective diaries and interviews, although some difficulties were pointed out, the statements of the students regarding their development came to the fore. In addition, it was pointed out that argumentation contributes not only to students’ academic writing skills, but also their development of thinking, objectivity, research motivation and critical thinking.